EFFECTS OF CHATGPT INTEGRATION AS AN ARTIFICIAL INTELLIGENCE TOOL FOR EDUCATION AND RESEARCH: AN EXPLORATORY SURVEY AT THE UNIVERSITY LEVEL - Syed Ghazanfer Abbas; Muhammad Ehsan; Dr. Gulnaz Akbar; Adeela Rehman; Haleema Bibi; Zohaib Hassan Sian (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
The purpose of this project is to investigate the outcomes of using ChatGPT as an AI tool for university-level instruction and research. The three specific goals of this study are to: (1) To determine the level of awareness and familiarity of ChatGPT among university students and faculty members; (2) To assess the perceived benefits and drawbacks of using ChatGPT as an artificial intelligence tool for educational and research activities; and (3) To investigate the willingness of students and faculty to use ChatGPT in this capacity. This study used a self-administered questionnaire and an exploratory survey approach. 200 university students and faculty members made up the sample; they were chosen using convenience sampling. Data were examined using descriptive statistics and content analysis, and the questionnaire included both closed-ended and open-ended items. According to the results, the majority of respondents were aware of and familiar with ChatGPT as an AI tool to varying degrees. Additionally, the respondents perceived ChatGPT as a useful and easy-to-use tool for enhancing teaching and research. Furthermore, the results indicated that ChatGPT integration had a positive impact on the quality of education and research outcomes. The study concludes that integrating ChatGPT as an AI tool can enhance the quality of education and research outcomes at the university level. The results suggest that universities should consider integrating ChatGPT into their educational and research programs to enhance the learning and research experiences of their students and faculty.